ELECTRONIC-STRUCTURE OF HETEROAROMATIC MOLECULES - ABINITIO CALCULATIONS AND PHOTOELECTRON-SPECTRA FOR ISOMERIC-OXAZOLES AND SOME ISOMERIC-OXADIAZOLES - Palmer, M; Findlay, R; Egdell, R (1977)
The UV photoelectron spectra are reported for isoxazole and 1,3,4-oxadiazole (He(I) region), oxazole and 1,2,5-oxadiazole (He(I) and He(II) regions). Marked fine structure is apparent on some of the spectra. The spectra have been assigned on the basis of ab initio calculations, and by comparison with the azoles and thiazoles. Variations in the lone pairs levels at O-, S- and N- across the azoles, oxazoles, thiazoles and azines are discussed. It is suggested that "through-bond" interactions are more widespread in the azines than previously noted. © 1977.